THE EFFECT OF DISCHARGE PLANNING ON PATIENT SATISFACTION: A SYSTEMATIC REVIEW - Liani Br Ginting; I Nyoman Ehrich Lister; Ali Napiah Nasution; Elis Anggeria; Rizky Aditya Hutomo (Nurse and Holistic Care, 2025)
Background: Discharge planning is a continuous process carried out by nurses to help patients prepare for self-care after leaving the hospital. It involves collaboration among healthcare providers, patients, and families. Through health education, discharge planning provides essential information about the disease and its management to reduce the risk of relapse and rehospitalization. Objective: This systematic review aims to identify the effect of discharge planning implementation on patient satisfaction in the inpatient room. Design: This study employed a systematic review design to synthesize empirical evidence on the effect of discharge planning implementation on patient satisfaction in hospital inpatient settings. Data Sources: A systematic literature search was conducted using two electronic databases: Google Scholar and ScienceDirect. Articles published between January 2020 and April 2025 were identified using the keywords (“discharge planning” OR “discharge process” OR “transitional care”) AND (“patient satisfaction” OR “patient experience” OR “patient-reported experience”) AND (“hospital” OR “inpatient”). Review Methods: A total of 717 articles were initially identified. After removing duplicates and applying inclusion and exclusion criteria—full-text availability, English or Indonesian language, and quantitative study design—15 studies were included in the narrative synthesis. Article selection followed the PRISMA guidelines to ensure transparency and methodological clarity. The included studies were analyzed narratively to identify patterns, key themes, and overall effects of discharge planning on patient satisfaction. Results: Based on the results of several articles that fit the inclusion criteria, the implementation of discharge planning has a significant influence on the level of patient satisfaction. Conclusion: The implementation of discharge planning plays a crucial role in the hospital service system. Discharge planning can increase patient satisfaction with hospital services. Hospitals should develop standardized discharge planning protocols, strengthen nurse training programs, and ensure patient-centered implementation.